2011
DOI: 10.1007/s10549-011-1842-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a large rearrangement in PALB2 in Spanish breast cancer families with male breast cancer

Abstract: It has been demonstrated that monoallelic PALB2 (Partner and Localizer of BRCA2) gene mutations predispose to familial breast cancer. Some of the families reported with germline PALB2 mutations presented male breast cancer as a characteristic clinical feature. Therefore, we wanted to investigate the contribution of germline PALB2 mutations in a set of 131 Spanish BRCA1/BRCA2-negative breast/ovarian cancer families with at least one male breast cancer case. The analysis included direct sequencing of all coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 31 publications
6
32
1
6
Order By: Relevance
“…7 Additional studies found carriers of truncating mutations with a frequency of ~1−2% in Spanish, Chinese, South African, Russian, German, Italian, AfricanAmerican, Australasian, and Malaysian familial or early-onset breast cancer cases. 10,[20][21][22][23][24] A similar frequency was observed in population-based studies of Australians and mixed-ethnicity breast cancer cases. 20,25,26 A mutation-carrier frequency of 3.4% was reported in familial cases from the United States.…”
Section: Introductionsupporting
confidence: 78%
“…7 Additional studies found carriers of truncating mutations with a frequency of ~1−2% in Spanish, Chinese, South African, Russian, German, Italian, AfricanAmerican, Australasian, and Malaysian familial or early-onset breast cancer cases. 10,[20][21][22][23][24] A similar frequency was observed in population-based studies of Australians and mixed-ethnicity breast cancer cases. 20,25,26 A mutation-carrier frequency of 3.4% was reported in familial cases from the United States.…”
Section: Introductionsupporting
confidence: 78%
“…The question of whether loss-of-function mutations in PALB2 confer a predisposition to ovarian cancer will require larger studies to address. We also estimated that the risk of breast cancer for male PALB2 mutation carriers is increased by a factor of 8, which is consistent with previous reports, 7,35,36 but the confidence interval for this estimate was very large. PALB2 loss-of-function mutations have been shown to confer a predisposition to pancreatic cancer, 37,38 but the lifetime risk in carriers has yet to be quantified.…”
Section: Discussionsupporting
confidence: 91%
“…Alu sequences were involved in all detected rearrangements. To date, a large rearrangement in PALB2 was detected only in a breast cancer family in Spain (28) and in a Canadian patient affected with breast and pancreatic cancer (35).…”
Section: Discussionmentioning
confidence: 99%